Using GIS And Geophysics In Selecting Suitable Basins With Freshwater Aquifers For An Efficient Exploration Strategy - A Case Study From Petra-Region, Jordan (2015)
In this study, an effective and time-saving strategy for groundwater exploration in alluvium basins in arid-semiarid lands was applied by integrating GIS and geophysics. Three steps were followed to locate productive local groundwater aquifers prone to annual recharge in the Region of Petra, which covers an area of 800 km². In the first step, geological, structural and geomorphological knowledge was applied to determine the parts of the sedimentary basin having potentials of being local groundwater aquifers. Some locality of the selected area with suitable hydrological conditions for recharge was chosen for an optimization process using GIS. In the second step, the selected locality of the basin was given emphasize on its detailed geology and hydrology to choose suitable locality for applying gravity visualization. Evaluation of this data leads to step number three. Now at localities with promising conditions vertical electrical soundings was applied to enable the authors to determine productive and renewable groundwater aquifers. As it is known that geophysical methods are considered as expensive and time-consuming work, therefore, in this strategy of groundwater surveying a special attention is given to budgets of time, efforts and funds constraints ResumenEn este estudio se aplicó una estrategia efectiva y eficaz para la exploración de aguas subterráneas en cuencas con depósitos aluviales para terrenos áridos y semiáridos a través de la integración del Sistema de Información Geográfica (GIS, inglés) y herramientas geofísicas. Se siguieron tres pasos para localizar acuíferos locales de aguas subterráneas propensos a las recargas anuales en la región de Petra, que cubre un área de 800 km2. En el primer paso se aplicó el conocimiento teórico para determinar las partes de la cuenca sedimentaria con el potencial de ser un acuífero local de aguas subterráneas. Se escogió una de las localidades del área seleccionada con condiciones hidrológicas apropiadas de recarga para un proceso de optimización con el GIS. En el segundo paso se hizo énfasis en la geología e hidrología detallada de la localidad seleccionada de la cuenca para así escoger un lugar apropiado para la aplicación del método de visualización gravitacional. La evaluación de los datos condujo el estudio al tercer paso. Se realizaron sondeos eléctricos en los lugares con evidencias para permitirle a los autores determinar los depósitos de aguas subterráneas productivos y renovables. Si bien los métodos geofísicos son considerados costosos y demandantes de tiempo, con esta estrategia de exploración de aguas subterráneas se hizo un énfasis especial a los presupuestos de tiempo, esfuerzo y limitaciones de fondos.